Exploring natural variation of Pinus pinaster Aiton using metabolomics: Is it possible to identify the region of origin of a pine from its metabolites? - Meijón, Mónica; Feito, Isabel; Oravec, Michal; Delatorre, Carolina; Weckwerth, Wolfram; Majada, Juan; Valledor, Luis (Molecular ecology, 2016)
Natural variation of the metabolome of Pinus pinaster was studied to improve understanding of its role in the adaptation process and phenotypic diversity. The metabolomes of needles and the apical and basal section of buds were analysed in ten provenances of P. pinaster, selected from France, Spain and Morocco, grown in a common garden for 5 years. The employment of complementary mass spectrometry techniques (GC-MS and LC-Orbitrap-MS) together with bioinformatics tools allowed the reliable quantification of 2403 molecular masses. The analysis of the metabolome showed that differences were maintained across provenances and that the metabolites characteristic of each organ are mainly related to amino acid metabolism, while provenances were distinguishable essentially through secondary metabolism when organs were analysed independently. Integrative analyses of metabolome, environmental and growth data provided a comprehensive picture of adaptation plasticity in conifers. These analyses defined two major groups of plants, distinguished by secondary metabolism: that is, either Atlantic or Mediterranean provenance. Needles were the most sensitive organ, where strong correlations were found between flavonoids and the water regime of the geographic origin of the provenance. The data obtained point to genome specialization aimed at maximizing the drought stress resistance of trees depending on their origin.
Keywords: období sucha; Morocco; metabolomika; Droughts; Metabolomics; fyziologická adaptace; Maroko; metabolom; Chromatography, High Pressure Liquid; adaptation; Španělsko; vysokoúčinná kapalinová chromatografie; Pinus; Metabolome; abiotic stress; UPLC-Orbitrap-MS; Spain; GC-MS; terpenoids; plynová chromatografie s hmotnostně spektrometrickou detekcí; Francie; conifers; France; borovice; flavonoids; Gas Chromatography-Mass Spectrometry; Adaptation, Physiological